APRESENTAÇÃO DOS CADERNOS DO IL 50 - Solé, Alessandra Santos; de Los Santos, Bruna da Rosa; Habel, Jussara Maria; Medeiros, Laís Virgínia Alves; Ferreira, Melissa Osterlund; Alquatti, Raquel; Garbin, Stefany Rettore (Cadernos do IL, 2017)
Apresentação do nº 52 dos Cadernos do IL - Estudos Linguísticos.